Data for the PhD thesis "Modeling lexical fields for translation: a corpus-based study of Armenian, German, and English culinary Verbs" - Dallakyan, Meri (Universität, 2025)
This dataset contains in high resolution all graphical visualizations of data analysis provided in my doctoral dissertation. The graphs are organized according to chapters and subchapters and titeled respectively. Additionally, this dataset provides all dataframes (German, English, and Armenian) in XLSX format of the manual semantic annotation based on which the graphs are generated. Among presented graphical visualizations are (Multiple) Correspondence Analysis (MCA vs. CA), Mosaic-Plots, Conditional Infererence Trees (CIT), and Context-Conditional Correlations Graphs (CCCG).
Gesehen am 07.08.2025
Keywords: Forschungsdaten; Datenbank